2014
DOI: 10.1104/pp.114.238071
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Brassica napus Low-Molecular Mass Acyl-Coenzyme A-Binding Protein in Arabidopsis Alters the Acyl-Coenzyme A Pool and Acyl Composition of Oil in Seeds      

Abstract: Low-molecular mass (10 kD) cytosolic acyl-coenzyme A-binding protein (ACBP) has a substantial influence over fatty acid (FA) composition in oilseeds, possibly via an effect on the partitioning of acyl groups between elongation and desaturation pathways. Previously, we demonstrated that the expression of a Brassica napus ACBP (BnACBP) complementary DNA in the developing seeds of Arabidopsis (Arabidopsis thaliana) resulted in increased levels of polyunsaturated FAs at the expense of eicosenoic acid (20:1 cisD11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…On acyl-CoA profiling, the acbp6 knockout mutant demonstrated an accumulation of unsaturated C18-CoAs in developing seeds and seedlings[32] consistent with previous observations on transgenic Arabidopsis seeds overexpressing the 10-kDa B.napus ACBP[86]. The variation in acyl-CoA composition of the double/triple mutants may ultimately affect seed development and germination.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…On acyl-CoA profiling, the acbp6 knockout mutant demonstrated an accumulation of unsaturated C18-CoAs in developing seeds and seedlings[32] consistent with previous observations on transgenic Arabidopsis seeds overexpressing the 10-kDa B.napus ACBP[86]. The variation in acyl-CoA composition of the double/triple mutants may ultimately affect seed development and germination.…”
supporting
confidence: 80%
“…However, some recent studies have shown that plant ACBPs are also involved in the biosynthesis of neutral lipids such as TAG in Arabidopsis seeds [32,68,82,86]. In mammals, ACBPs have been shown to affect TAG accumulation [39,144,194].…”
Section: Plant Acyl-coa-binding Proteins In Lipid Metabolismmentioning
confidence: 97%
See 2 more Smart Citations
“…4). The activity of microsomal DGAT activity has been shown to be activated by proteins such as acyl-CoA-binding protein, bovine serum albumin, and human acylation-stimulating protein (Hobbs and Hills, 2000;Little et al, 1994;Weselake et al, 2000;Yurchenko et al, 2014), although specific plant regulatory proteins modulating DGAT1 has yet to be identified. Furthermore, microsomal DGAT activity in Arabidopsis was inhibited by niacin (Hobbs and Hills, 2000); this compound was later shown to noncompetitively inhibit mouse DGAT2 (Ganji et al, 2004).…”
Section: Regulation Of Dgatmentioning
confidence: 99%